2017
DOI: 10.1149/2.0351712jss
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ce3+Ions in Achieving High Silicon Nitride Polish Rates

Abstract: We show that Ce 3+ ions when used as an additive to ceria dispersions enhance plasma-enhanced chemical-vapor-deposited silicon nitride polish or removal rates (RRs). Ceria slurries (0.1 wt% and 140 nm avg. size) containing 2.3 mM Ce(NO 3 ) 3 and no other additive gave nitride RRs of ∼300 nm/min at 4 psi and ∼350 nm/min at 5 psi, both at pH4. The nitride RRs measured in the presence of Ce(NO 3 ) 3 , Ce(CH 3 COO) 3 and KNO 3 suggest that the rate enhancement is solely due to the presence of Ce 3+ ions. We discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The trivalent state of cerium promotes Ce-O-Si bonding with an enhancement of the interaction between ceria particles and silicon dioxide wafer. Since the formation of Ce-O-Si bonding in an oxide CMP using ceria abrasives is directly related to the material removal rate, high concentrations of Ce 3+ ions can provide high CMP performance 18 , 21 , 57 . Figure 4 shows CMP performance including the removal rate and finished surface roughness of the oxide film using photo-reduced ceria nanoparticles according to UV irradiation time.…”
Section: Resultsmentioning
confidence: 99%
“…The trivalent state of cerium promotes Ce-O-Si bonding with an enhancement of the interaction between ceria particles and silicon dioxide wafer. Since the formation of Ce-O-Si bonding in an oxide CMP using ceria abrasives is directly related to the material removal rate, high concentrations of Ce 3+ ions can provide high CMP performance 18 , 21 , 57 . Figure 4 shows CMP performance including the removal rate and finished surface roughness of the oxide film using photo-reduced ceria nanoparticles according to UV irradiation time.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the mechanism of Si 3 N 4 removal rate suppression will be discussed in detail. Later, Alety et al showed that the removal rate of Si 3 N 4 film in the presence of 0.1 wt% ceria particles + 2.3 mM Ce(NO 3 ) 3 at pH 4 was ∼300 nm/min, whereas it is ∼10 nm/min with only ceria particle [55]. X-ray photoelectron spectroscopy of the polished Si 3 N 4 films is similar to that of an as-received silicon oxynitride film which led them to suggest that, in the presence of Ce 3+ , the surface of Si 3 N 4 film can be converted to silicon oxynitride which was then polished at a high rate [55].…”
Section: Chemical Reactions Between Slurries and Dielectric Filmsmentioning
confidence: 99%
“…34 The Ce 3+ -rich CeO 2 can reduce the formed oxide to eliminate oxygen atoms from SiO 2 , resulting in an improved MRR in pH 9 with a smooth polished surface. 35 Next, the dependence of the material removal characteristics on the polishing rotation rate was examined to obtain a further improved MRR. For conventional polishing, the MRR is proportional to the relative velocity between the material and the polishing tool, which is known as Preston's law of polishing.…”
Section: Polishing Characteristics Of the Double-layered Polishing Pad-mentioning
confidence: 99%